The grasping hand structural and functional anatomy of the hand and upper extremity - Gupta, Amit; Tamai, Makoto (Thieme, 2021)
Anatomical guide leverages exceptional dissection images to elucidate the biomechanics of the hand and upper extremity The hand is a unique instrument that executes the commands of the brain and expresses the nuances of the mind. The Grasping Hand: Structural and Functional Anatomy of the Hand and Upper Extremity by Amit Gupta and Makoto Tamai is a state-of-the-art book that details the functions of the hand to feel, receive, gather, collect and hold, as well as the complex role that the whole upper extremity plays in enabling these actions. The anatomical structures intrinsic to these functions are detailed through illuminating cadaveric dissections and succinct text. Organized in 5 sections and 38 chapters, the book begins with a chapter detailing the intriguing history of hand anatomy, followed by a section encompassing the structural and functional fundamentals. The third section covers general anatomy and function, with discussions of the nerves and vascularity of the upper extremity, as well as the brachial plexus. The fourth section features 26 anatomically organized chapters from the shoulder to the fingertip with anatomical and functional insights on the joints, fascia and retinacula, interosseus membrane, tendons and more. The single chapter comprising the final section covers imaging and anatomy. Key Highlights Pioneers in modern hand surgery share vast collective knowledge and pearls on hand and upper extremity anatomy and biomechanics Over 1,100 exquisite, original dissections of lightly embalmed fresh cadaveric arms provide unique visual insights about underlying tissues and structures High quality, never before published original photographs enhance understanding of anatomy, physiology, and pathology This practical resource is ideal for reviewing anatomy and biomechanics prior to performing hand, wrist, arm, elbow, and shoulder
Keywords: Upper Extremity - anatomy & histology; Upper Extremity - physiology; Bones of Upper Extremity - anatomy & histology; Bones of Upper Extremity - physiology